2009
DOI: 10.1007/s10886-009-9637-1
|View full text |Cite
|
Sign up to set email alerts
|

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity

Abstract: Larkspurs (Delphinium spp.) are poisonous plants found on rangelands in western North America. Larkspur's toxicity has been attributed to the norditerpenoid alkaloids, which are divided into two main structural groups: the highly toxic (N-methylsuccinimido) anthranoyllycoctonine type (MSAL type) and the less toxic 7,8-methylenedioxylycoctonine type (MDL type). Plants high in the MSAL-type alkaloids are thought to be the most toxic to cattle, and the concentrations of these alkaloids have been used as a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Structure‐function studies of norditerpenoid alkaloids have shown that the aromatic ester functional group on MLA is a significant haptophore, and that the succinimide group imparts significant toxicity to the alkaloids ,. Current research interest in larkspur alkaloids includes the identification of new alkaloids, [24,25], species alkaloid composition, risk assessment, and the study of biological activities in rats and insects ,…”
Section: Delphinium Spp Norditerpenoid Alkaloidsmentioning
confidence: 99%
“…Structure‐function studies of norditerpenoid alkaloids have shown that the aromatic ester functional group on MLA is a significant haptophore, and that the succinimide group imparts significant toxicity to the alkaloids ,. Current research interest in larkspur alkaloids includes the identification of new alkaloids, [24,25], species alkaloid composition, risk assessment, and the study of biological activities in rats and insects ,…”
Section: Delphinium Spp Norditerpenoid Alkaloidsmentioning
confidence: 99%
“…Additionally, another tall larkspur species, D. stachydeum only contains non MSAL-type alkaloids [18]. Likewise in D. occidentale there are two chemotypes, one that contains both MSAL and non MSAL-type alkaloids and one that does not contain MSAL-type alkaloids [19]. Each chemotype has a distinct geographic distribution shown in Figure 3.…”
Section: Plant Ecology and Distributionmentioning
confidence: 99%
“…Even in the absence of chromatography, a simple flow injection mass spectrometry method can be a valuable tool in assessing the alkaloid composition of larkspurs [42]. Such flow injection methods have been valuable in chemo-typing the various larkspurs based on alkaloid profiles, geographical location and species identifications [17][18][19]. With development of fully hyphenated methods, such as LC-MS/MS, the sensitivity and selectivity have become sufficient for detection of very low concentration of alkaloids (i.e., ng/mL) in such samples as sera or tissue (liver) for the purposes of defining toxicokinetics [22,45,46] or for diagnostic purposes in the analysis of contaminated feed supplies, tissues, rumen content or fluid samples of poisoned animals ( Figure 4).…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of herbarium specimens for reconstructing phenological changes associated with climate warming is well established [17][18][19] . Herbarium specimens have also been used in the fields of chemical ecology 20,21 , pollination ecology 22,23 and insectplant interactions 24 . With the advent of molecular systematics, the protocols for DNA isolation from herbarium specimens have been standardized 25,26 , and DNA extraction protocols from herbarium specimens of vascular plants as old as 200 years have been achieved.…”
mentioning
confidence: 99%